Morfogenesis Anggrek Dendrobium ‘Gradita 31’ dengan Penggunaan Benzyladenine atau Thidiazuron - Hamiranti, Rahmadyah; Prajaka, Nanang Wahyu; Yeni, Yeni; Erfa, Lisa; Maulida, Desi (Politeknik Negeri Lampung, 2023)
Dendrobium Gradita 31 has superior characteristics that are in demand by the market in Indonesia, so seeds with sameness quality, the same characteristics as the parent and in large quantities are needed. Tissue culture is one solution to support the availability of seeds in large quantities and have a high level of sameness quality. The process of regulating the type of ZPT and concentration in the culture media does not always produce the same regeneration pathway. This research aims to determine the regeneration pathway and to obtain the best type and concentration of cytokinin to support its regeneration pathway. This study used a completely randomized design with 3 replications. The first factor is the type of cytokinin, BA and Tdz. The second factor is the concentration of Benzyladenine and Thidiazuron, 1, 2 and 3 mg/l.. The data was analyzed using analysis of variance, and mean value was tested using tukey test 5%. The results of this study indicate that the regeneration pathway in the formation of adventitious shoots was indirect embryogenesis. The use of Tdz 3 mg/l was able to produce the highest percentage of somatic embryo formation and the highest number of somatic embryos. The fastest shoot formation time, shoot formation percentage and the highest number of shoots per clump were found BA 2 mg/l.